PELAKSANAAN PRINSIP KERJA SAMA DALAM PERCAKAPAN GURU DAN SISWA SERTA DAMPAKNYA TERHADAP PEMBELAJARAN BAHASA INDONESIA DI KELAS XI SMAN I KEDIRI - Ni Wayan Eminda Sari (Jurnal Santiaji Pendidikan (JSP), 2013)
This study aimed at gathering illustrations and explanation about (1) learning context as a field of the implementation for cooperative principle in a classroom learning, (2) the cooperative principle conducted by the teacher, (3) the implementation of cooperative principle conducted by the students, (4) the effects of cooperative principle which is conducted by teacher and students upon Indonesian learning in the class XI SMAN 1 Kediri. In order to achieve these goals, this study uses the descriptive-qualitative design. The subject of the study is the students and Indonesian teacher at the class XI SMAN 1 Kediri. The data gathering is conducted by the methods of recording, observation, and interview. The data gained then was analyzed qualitatively descriptive that covers four phases, namely data gathering, data reduction, data presentation, verification, and conclusion making. The results of this study shows that learning context as the field of cooperative principle implementation in the classroom, dominantly appears in formal situation, and appears also in semi-formal and non-formal situation. The cooperative principle conducted by the teacher is marked by teacher’s speech that obeyed the maxim of quantity, maxim of quality, maxim of relevance, and maxim of manner. The implementation of cooperative principle conducted by the students is marked by teacher’s speech that obeyed the maxim of quantity, maxim of quality, maxim of relevance, and maxim of manner. The effects that appear due to the implementation of cooperative principle upon Indonesia is that the situation of the learning in the classroom become conducive and comfortable, students’ activity is developed, the learning runs well without any disturbances, and the goals of the teaching can be achieved effectively. Based on the result of this study, the readers expected to realize that in the use of speech, cooperative principle needs to be considered so that the conversation can be more effective and efficient.